PREDICTION OF RESIDENTIAL AREA DEVELOPMENT IN LEMBANG DISTRICT IN 2028 USING NEAREST NEIGHBOR ANALYSIS AND CELLULAR AUTOMATA-LOGISTIC REGRESSION - Indriyani, Astri (JURNAL GEOGRAFI, 2025)
Population increase and swift growth in the Lembang District have led to considerable effects on land use alterations and a decline in vegetation. As a result, this research seeks to examine: 1) changes in land use in Lembang District in 2008-2023, 2) predictions of residential area development, 3) predictions of settlement development patterns. The approach applied involves Nearest Neighbor Analysis to examine the trends and pathways of regional growth in Lembang District, along with the Cellular Automata-Logistic Regression model utilized for forecasting shifts in land utilization in Lembang District. Findings from the investigation into land use alterations reveal transformations from agricultural areas to residential zones, with a total change area of 292.67 Ha and changes in dry fields/fields to plantations covering an area of 562.57 Ha. Then the prediction of settlement development in 2028 increased by 123.62 Ha or increased by around 8% with a kappa correction validation result of 97%. Based on the outcomes of the settlement forecast, a study was conducted on the settlement distribution trend. The findings from this study indicate that the anticipated settlement distribution trend that settlements form a clustered pattern.